2016
DOI: 10.1007/s11769-016-0800-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nature reserves for natural forests protection in tropical Hainan: a 20 year analysis

Abstract: Abstract:The establishment of nature reserves is a key approach for biodiversity conservation worldwide. However, there is a lack of unified methodology to evaluate the effectiveness of nature reserves, particularly in China, the world′s most populous nation supporting some of the most valuable biodiversity hotspots in the world. In this study, we conducted a long-term and large-scale analysis of the effectiveness of 20 of the earliest nature reserves established in Hainan Province, an island home to among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Therefore, it is vital to establish protected areas in remote rugged mountains as early as possible, where vegetation grows naturally with minimal influence from anthropogenic activities. Considering the limited data used in the vegetation analysis in this study, in the next step, we will further study the vegetation in protected areas using time-series images and more parameters, e.g., classified vegetation categories [12], biophysical parameters, landscape indices, and carbon sink. Meanwhile, the data from exterior influence factors of meteorology [59,60], economy, and society will be discussed.…”
Section: Vegetation Of Protected Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is vital to establish protected areas in remote rugged mountains as early as possible, where vegetation grows naturally with minimal influence from anthropogenic activities. Considering the limited data used in the vegetation analysis in this study, in the next step, we will further study the vegetation in protected areas using time-series images and more parameters, e.g., classified vegetation categories [12], biophysical parameters, landscape indices, and carbon sink. Meanwhile, the data from exterior influence factors of meteorology [59,60], economy, and society will be discussed.…”
Section: Vegetation Of Protected Areasmentioning
confidence: 99%
“…The terrestrial vegetation plays an important role in biodiversity conservation, ecological sustainability, and in achieving carbon neutrality [1][2][3][4]. Protected areas are useful for natural vegetation growth and mitigating vegetation degradation and deforestation [5][6][7][8][9][10][11][12], since they suffer minimal eco-society environmental stress from human beings [13,14]. Thus, it is significant to monitor the vegetation growth of protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment and effective management of nature reserves can enhance natural vegetation coverage and improve both the local ecological environment quality and the aesthetic appeal of landscapes [32,33]. Furthermore, Yu et al employed transition matrix analysis and principal component analysis to demonstrate that nature reserves significantly mitigate the loss of Hainan's natural forests [34]. Scharsich observed that the land cover composition of Matobo National Park in Zimbabwe remained largely stable from 1989 to 2014.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have considered the concomitant roles of both size and management category as measurable indicators of reserve conservation performance (Joppa, Loarie & Pimm, 2008;Peres, 2011;Miranda et al, 2016). More often researchers have focused on the patterns of land-use and human economic activities within and around each PA (DeFries, Karanth, & Pareeth 2010;Beresford et al, 2013;Pfaff et al, 2015;Bowei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed georeferenced data on species richness and diversity are only available at selected sites, either within or outside reserves, and most studies use deforestation (or the lack thereof) as the proxy of protected area performance in preserving forest biodiversity (e.g. Nepstad et al 2006, Beresford et al 2013, Paiva et al 2015, Pfaff et al 2015, Ren et al 2015, Bowei et al 2016, Miranda et al 2016. Here, we provide a quantitative assessment of the degree to which the natural vegetation cover of 788 Brazilian forest reserves within the Amazonian and the Atlantic Forest domains have been converted into different patterns of land use.…”
mentioning
confidence: 99%